Digital Literacy in the Development of Community-Based Tourism in Tamansari District, Bogor Regency - Gati Dwi Yuliana; Retor A. W. Kaligis; Benedictus Helpris Estaswara; Sudarto; Evana Widyasiwi (Jurnal Penelitian, 2026)
This study focuses on the digital literacy of Tamansari tourism village business actors in building and developing community-based tourism villages. This research was conducted qualitatively by conducting focus group discussions (FGD) with 14 people consisting of representatives of the sub-district/village government and tourism village actors in Tamansari, Pasir Eurih, and Sukajadi. The results of the study show that digital literacy and fluency in tourism village marketing communication practices are divided into four categories. The first category is filled by tourism village actors who have digital fluency at the level of being able to utilize social media, especially Facebook, to promote tourism villages simply because it is still done manually. The second category is filled by tourism village actors who have digital fluency at the level of learning content editing practices. The third category is filled by tourism village actors who have digital fluency at the level of being able to create photo uploads that have been equipped with information about price descriptions and business addresses of products and/or services related to tourism village. The fourth category is filled by village tourism actors who possess digital fluency, capable of using multiple social media platforms simultaneously, implementing strategies for managing upload times and coordinating online with other village tourism business actors.